Enjoying food without caloric cost: The impact of brief mindfulness on laboratory eating outcomes. (April 2016) - Arch, Joanna J.; Brown, Kirk Warren; Goodman, Robert J.; Della Porta, Matthew D.; Kiken, Laura G.; Tillman, Shanna
Abstract: Objective: Mindfulness-based interventions have been increasingly applied to treat eating-related problems ranging from obesity to eating disorders. Yet few studies have empirically examined the mechanisms of a mindful approach to eating. The current studies examine the potential of brief mindfulness instructions to enhance the psychological and behavioral dimensions of eating. Methods: In three experiments (total N = 319 undergraduates), we examined whether brief mindfulness instructions would enhance the positive sensory experience involved in tasting food as well as healthy eating behaviors. Results: Relative to distraction control instructions, the first two studies demonstrated that brief mindfulness instructions increased the enjoyment of a commonly pleasurable food (chocolate; Study 1), and a food with generally more mixed associations (raisins; Study 2). The third study replicated and extended these findings to show that brief mindfulness instructions also led to lower calorie consumption of unhealthy food relative to distracted or no-instruction control conditions, an effect mediated by greater eating enjoyment. Conclusions: Findings demonstrated the power of brief mindfulness instructions to positively impact both health-relevant behavior and sensory experience associated with eating food. Implications for both theory and clinical applications of mindfulness are discussed. Highlights: We assessed the sensory and behavioral benefits of tasting food mindfully. Across two lab studies, brief mindfulness enhanced enjoyment of tasting food. Brief mindfulness led to lower caloric consumption of 'junk' foods. Greater tasting enjoyment mediated the impact of mindfulness on lower consumption. These studies suggest potential benefits of mindfulness in the context of eating.